Response of soybean genotypes to Alectra vogelii infestation under natural field conditions - Kureh, I.; Alabi, S.; Kamara, A. (2005)
Field studies were conducted in 1995 and 1996 in the northern Guinea savanna of Nigeria to determine the response of 22 soybean genotypes to Alectra infestation. Significant differences were observed amongst soybean genotypes in number of Alectra shoots that emerged at 9 and 10 weeks after sowing and days to first Alectra emergence. Alectra emergence occurred later in early maturing soybean genotypes [54 days after sowing (DAS)] while with most late maturing genotypes, Alectra emergence started at 50 DAS. Result revealed that sixteen genotypes supported few or no Alectra shoots while six were susceptible. Soybean genotypes that supported high numbers of Alectra shoots recorded lower grain yields than those with fewer Alectra shoots. However, soybean genotypes, SAMSOY2 and TGX1485-1D that significantly supported high numbers of Alectra recorded grain yields similar to those of genotypes that supported few or no Alectra. These findings may be due to three possible mechanisms of resistance of soybean genotypes to Alectra parasitism. The sixteen genotypes, which supported few or no Alectra shoots, may have produced lower amounts of root exudates required for stimulation of germination of Alectra. They may also have prevented the initiation, attachment, and penetration of haustorium from Alectra plants to the roots of the hosts. These mechanism were however, not investigated in this study. Further studies may therefore be necessary to confirm our speculations. Soybean genotypes, SAMSOY2 and TGX1485-1D, which recorded high yield irrespective of high infestation with Alectra may exhibit tolerance to the parasite.